Research of structural changes in the molding of thermoplastic slip beryllium oxide in flat spinneret - Zhapbasbayev, U.K.; Ramazanov, G.I.; Sattinova, Z.K. (Recent Contributions to Physics, 2012)
The results of modeling of ceramic forming process by the hot casting method are illustrated. Mathematical model describes the motion of liquid thermoplastic ceramic slurry in molding cavity subject to solidification. Casting characteristics, which providing uniform property of ceramics in forming process by the hot casting method, are determined.
Keywords: thermoplastic slip, pottery, hot casting method, a mathematical model